2018
DOI: 10.1038/s41419-018-0924-z
|View full text |Cite
|
Sign up to set email alerts
|

MRE11 inhibition highlights a replication stress-dependent vulnerability of MYCN-driven tumors

Abstract: MRE11 is a component of the MRE11/RAD50/NBS1 (MRN) complex, whose activity is essential to control faithful DNA replication and to prevent accumulation of deleterious DNA double-strand breaks. In humans, hypomorphic mutations in these genes lead to DNA damage response (DDR)-defective and cancer-prone syndromes. Moreover, MRN complex dysfunction dramatically affects the nervous system, where MRE11 is required to restrain MYCN-dependent replication stress, during the rapid expansion of progenitor cells. MYCN act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 55 publications
4
40
0
Order By: Relevance
“…In models of Ras-or MYC-driven cancer, signalling through these oncogenes has been shown to lead to sensitivity to ATR inhibition [54][55][56]. In NB cell lines, high MYCN expression has been shown to increase RS [32,57]. Here we have shown that amplification and overexpression of the MYCN oncogene in NB cell lines is associated with sensitivity to VE-821, confirming that MYCN driven NB cells are vulnerable to ATR inhibition.…”
Section: Discussionsupporting
confidence: 68%
“…In models of Ras-or MYC-driven cancer, signalling through these oncogenes has been shown to lead to sensitivity to ATR inhibition [54][55][56]. In NB cell lines, high MYCN expression has been shown to increase RS [32,57]. Here we have shown that amplification and overexpression of the MYCN oncogene in NB cell lines is associated with sensitivity to VE-821, confirming that MYCN driven NB cells are vulnerable to ATR inhibition.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, targeting DSB repair pathways is a potential effective strategy to enhance radio-sensitivity ( 4 6 , 8 , 11 ). As one of the most famous examples of HR inhibitors, mirin was developed against endonuclease activity of MRE11 and used to effectively inhibit multiple cancers ( 32 , 56 , 57 ). Similarly, NU7441, a highly selective inhibitor for DNA-PK, blocked NHEJ of radiation-induced DSBs and enhanced cancer radio-sensitivity ( 33 , 34 , 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Around 50% of HR-NB have an amplification of the MYCN oncogene, which drives proliferation and causes replication stress (117). MYCN also transcriptionally upregulates many proteins involved in DNA DSB repair, including components of the MRE11-RAD50-NBLS1 (MRN) complex (118,119), alternative NHEJ (alt-NHEJ) (120), and Bloom syndrome (BLM) helicase (121), and the cell cycle checkpoint protein CHK1 (117,122). Upregulation of these genes likely provide MYCNdriven tumors the ability to tolerate higher levels of DNA damage and replication stress.…”
Section: Ddr Defects In Neuroblastomamentioning
confidence: 99%